2012
DOI: 10.1177/1065912912469729
|View full text |Cite
|
Sign up to set email alerts
|

Toward an Actor-Based Measure of Supreme Court Case Salience

Abstract: Case salience affects nearly every aspect of Supreme Court justices' behavior, yet a valid actor-based measure of salience has remained elusive. Researchers have instead relied on external proxy indicators, such as amicus curiae participation and media coverage, to explain justices' behavior. We propose a novel measurement of salience in which we use justices' differential levels of engagement to generate actor-based measures of case and justice-level salience. Focusing on justices' behavior during oral argume… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…(Transcript of Oral Argument at 14, Hudson v. Michigan, 547 U.S. 586 ( 2006)). A non-substantive statement like Breyer's counts as a speech episode but constitutes random noise in our data (Black et al, 2013;Johnson et al, 2009). 13 To count the number of words and the number of turns, we included an observation in the dataset for each justice in each case (thus each case has nine distinct rows).…”
Section: Discussionmentioning
confidence: 74%
See 2 more Smart Citations
“…(Transcript of Oral Argument at 14, Hudson v. Michigan, 547 U.S. 586 ( 2006)). A non-substantive statement like Breyer's counts as a speech episode but constitutes random noise in our data (Black et al, 2013;Johnson et al, 2009). 13 To count the number of words and the number of turns, we included an observation in the dataset for each justice in each case (thus each case has nine distinct rows).…”
Section: Discussionmentioning
confidence: 74%
“…Michigan , 547 U.S. 586 (2006)). A non‐substantive statement like Breyer's counts as a speech episode but constitutes random noise in our data (Black et al, 2013; Johnson et al, 2009).…”
mentioning
confidence: 79%
See 1 more Smart Citation
“…In their analysis on persuasion at oral argument, Li and Pryor (2020) found that the grades influenced justices' votes. Black, Sorenson, and Johnson (2012) examined whether the Court asked more or fewer questions when faced with higher (lower) quality attorney arguments. Black et al (2016) used the measure when examining the effects of emotional language in party briefs.…”
Section: The Value Of Oral Argumentsmentioning
confidence: 99%